An Exploration of Students’ Perceptions of Teacher Feedback and Its Influence on Their Motivation to Learn English - Ubaidillah, Muhammad Farid; Jati, Sigit Pramono; Sugesti, Dzahina (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2026)
This study explores how students perceive teacher feedback and how it affects their motivation to learn English, with a specific focus on the acceleration class at MTsN 1 Surabaya. Adopting a mixed-method pragmatism with a qualitative descriptive approach, the research involved 31 students from the seventh grade, selected through purposive sampling. Data were gathered using a structured Google Form questionnaire consisting of 30 Likert-scale statements, 15 focused on teacher feedback and 15 on learning motivation. Descriptive statistics were used to highlight general response patterns, while thematic analysis helped interpret students’ perceptions in more depth. The findings show that students more to view their teacher's feedback in a positive light, describing it as clear, specific, and encouraging. This positive perception strongly correlates with higher motivation. The study suggests that effective feedback helps students feel more competent and confident, creates a psychologically safe environment where they are not afraid to make mistakes, and empowers them to take more ownership of their learning. While the results were largely positive, a small percentage of students expressed neutral views, indicating that feedback is not equally effective for everyone. The study concludes that teacher feedback is a crucial tool for building and sustaining student motivation. It recommends that educators focus on providing supportive and actionable feedback to foster a positive and productive learning atmosphere.